A functional single nucleotide polymorphism in ABCC11, rs17822931, is associated with the risk of breast cancer in Japanese. (18th March 2019) - Ishiguro, Junko; Ito, Hidemi; Tsukamoto, Megumi; Iwata, Hiroji; Nakagawa, Hiroshi; Matsuo, Keitaro
Abstract: The adenosine triphosphate-binding cassette (ABC) transporter superfamily consists of membrane proteins which translocate various substrates across membranes. Because ABCC11, a member ABC transporter, is highly expressed in breast cancer tissue, it may be involved in the efflux of conjugated estrogen metabolites. rs17822931, a functional single nucleotide polymorphism (SNP) in ABCC11, may play a role in the carcinogenesis of breast cancer via estrogen. Here, we aimed to evaluate the association between ABCC11 rs17822931 and breast cancer risk in a Japanese population. We conducted a case–control study in 697 patients with breast cancer and 1394 age- and menopausal status-matched controls within the framework of the Hospital-based Epidemiological Research Program at Aichi Cancer Center II (HERPACC II). The association was evaluated with odds ratios (ORs) and 95% confidence intervals (CIs) calculated using a conditional logistic model adjusted for potential confounders. In the per allele model, compared with the A allele, the G allele was inversely associated with breast cancer: OR, 0.77, 95% CI, 0.62–0.95 and P = 0.013. The stratified analyses showed that this polymorphism had a high impact on estrogen receptor (ER)-positive breast cancer risk and conditions assumed to correlate with high exposure to estrogen, namely no lactation and low soy intake. Our data showed that a significant association between rs17822931 and the risk of breast cancer, especially ER-positive breast cancer, in Japanese women. Compared to women with low estrogen efflux activity with the A allele, those with high efflux activity with the G allele may have a lower risk of breast cancer, particularly women with high estrogen exposure. Abstract : A single nucleotide polymorphism, rs17822931, on ABCC11 affects cellular estrogen efflux activity. We found a high activity allele in rs17822931 was significantly associated with a lower risk of breast cancer, particularly among those exposed with higher estrogen.